Note-taking strategies employed by level 3 students at International School, Vietnam National University, Hanoi while listening to the book Lecture Ready 2" - Nguyen, Thi Thu Huyen (University of Languages and International Studies, 2017)
This paper reports on note-taking strategies employed by Level 3 students (N=50) at International School, Vietnam National University, Hanoi while listening to the book ‘Lecture Ready 2’. The purpose of this study was threefold: To indicate whether all the (...)